The The Applicability of the Self-determined Learning Concept in Professional Education: A Self Study in In-service Teacher Education - Rafida Sahartaqiya (Journal of Education Research, 2026)
The Teacher Professional Education Program (PPG) delivered via Learning Management System (LMS) requires participants to fulfill dual roles as active teachers and learners, posing complex challenges for Self-Determined Learning (SDL) or heutagogy implementation. This study examines the suitability and effectiveness of SDL principles within LMS-based learning in PPG. Employing a descriptive qualitative approach with a sequential explanatory design, data were collected through open-ended questionnaires and semi-structured interviews with purposively selected participants. Findings indicate that LMS-based learning supports autonomy by enabling flexible access to materials, encouraging self-study, and facilitating integration of knowledge with professional experience. Nevertheless, SDL implementation was hindered by heavy workloads, limited study time, insufficient LMS interaction, and continued instructor dependence. These findings suggest that successful SDL implementation requires adaptive instructional designs, strengthened academic support, and appropriate facilitator guidance to sustain participants' professional development.